INCREASING THE Si/Al RATIO OF NATURAL ZEOLITE MORDENITE AS BASIC MATERIAL OF CATALYST - Handhoyo, Roocyta; Prijatama, Herry; Sofiyah, Siti; Nurlela, Iis; Yusianita, Nita; Amelia, R.; Komala, Ratna (Jurnal Zeolit Indonesia, 2005)
One of the application of zeolite as a multi-function mineral is the use as catalyst. Investigation to utilize Indonesian natural zeolite as a catalyst will increase the added value and gives a chance to reduce the dependency of imported catalyst. One of the main property, which allow zeolite to be used as a catalyst, is a high silica-alumina ratio, where Si/Al >10. As a preminalry stage to form a catalyst zeolite, research has been carried out to increase the Si/Al ratio of natural mordenite from Cikalong, Tasikmalaya. The method applied is dealumination process, which is followed by calcinations and ion exchange. This process is expected to modify the Na-zeolite from natural mordenit to be a NH4-zeolite which can be transformed to a catalyst zeolite. Dealumination process is carried out using HNO3, with variable concentration and time at temperature of 85°C. Thereafter, zeolite is calcined at 700°C and is followed ion exchange process using NH4NO3. The current stage of research has been succeeded to increase the Si/Al ratio of natural mordenite from Si/Al @ 5 to Si/Al > 10. The process condition applied is dealumination with 8N HNO3 for 24 hours at 85°°C and is followed by calcinations at 700°C for 2 hours. Ion exchange is proceeded with 5% NH4NO3 for 2 hours and is followed by another calcinations at 400°C for 2 hours.